PELATIHAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS ETNOMATEMATIKA BERBANTUAN SOFTWARE GEOGEBRA DI KECAMATAN PULAU LAKOR - Inuhan, Michael; Dahoklory, Andy S K; Lekitoo, John Nandito; Rupilele, Karolina; MA, Ratnah Kurniati; Sugiarto, Sigit (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2023)
One area in Southwest Maluku Regency that still maintains the culture of its people is Lakor District. Parts of culture that are still maintained today are Lakor weaving, traditional houses, lutur, traditional games, traditional dances, and others. On the other hand, mathematics learning in schools does not accommodate these diverse cultures. Ethnomathematics learning is a way of utilizing local culture as a means of introducing mathematical material. Ethnomathematics-based learning training activities with the help of Geogebra software were carried out with a percentage of 98.83%. Based on 10 indicators of implementation, this training activity is in the very good category and helps teachers make learning more creative and innovative